Treatment of aseptic necrosis of the femoral head. Clinical guidelines - A. N. Torgashin; S. S. Rodionova; A. A. Shumsky; M. A. Makarov; A. V. Torgashina; I. F. Akhtyamov; A. N. Kovalenko; N. V. Zagorodniy; S. P. Mironov (Научно-практическая ревматология, 2021)
Aseptic necrosis of bone is a serious disease that, if detected early and with adequate therapy, can be cured. Late diagnosis and lack of therapy leads to rapid joint destruction and patient disability. The proposed draft guidelines are a part of the National Clinical Guidelines for Aseptic Bone Necrosis (Osteonecrosis). Purpose of the study was creating an algorithm for diagnosing and treating osteonecrosis based on assessment of the level of evidence of literature data. The Guidelines reflect aspects of the clinical, instrumental and laboratory examination of patients with osteonecrosis, treatment options depending on the localization of the process and stage of the disease.